PERENCANAAN BANGUNAN JETTY DARI BAHAN BRONJONG DI MUARA SUNGAI SUNGGA PANTAI JASRI KABUPATEN KARANGASEM - Putu Gede Panji Oka Chandra; Cok Agung Yujana; I Ketut Yasa Bagiarta (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
Jasri Beach already has a protection structure in the form of a revetment which also functions to withstand wave overtopping. The tides and river discharge at the mouth of the Sungga River in Jasri Beach affect the spread of sediment floating in the water column and at certain times it can settle on the bottom of the water. Thus, the jetty planning at the mouth of the estuary aims to hold the longshore sediment which is pushed by the waves, into the estuary and then settles which can cause flooding at the mouth of the estuary. Based on the analysis of the jetty structure planning at the estuary of the Sungga River using gabion material, it is obtained: the height of the jetty (Eljetty) = 3 m, the weight of the first layer stone (W1) = 2.486 tons, the weight of the second layer (W2) = 0.2486 tons, the peak width (B) = 2.434 m, thickness of the first layer (t1) = 2.434 m, thickness of the second layer (t2) = 1.129 m, thickness of toe protection (ttoe) = 1.781 m, width of toe protection (Btoe) = 2.166 m, weight of toe protection stone (Wtoe) = 0.148 tons, and the estimated of cost construction is IDR 4,106,578,000.00.